Hubungan Intensitas Aktivitas Fisik dengan Kebugaran Kardiorespirasi dan Durasi Tidur Mahasiswa Pendidikan Olahraga - Mulyawan, Abdi; Santoso, Januar Abdilah; Jusuf, Jeane Betty Kurnia (Universitas Hamzanwadi, 2025)
The relationship between physical activity intensity, cardiorespiratory fitness and sleep duration has become a vital health issue among students. The aim of this research is to analyze the relationship between physical activity intensity, cardiorespiratory fitness and sleep time in sports students at Universitas Muhammadiyah Kalimantan Timur. Using a cross-sectional design, this research was conducted on a sample of 102 students (68 men, 34 women) aged 18 to 25 years, who were selected using stratified random sampling. Data were collected using the International Physical Activity Questionnaire (IPAQ) to assess the intensity of physical activity, the Multistage Fitness Test (MFT) to assess cardiorespiratory fitness, and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep duration. Pearson correlation and multiple linear regression were used in data analysis. The results showed that there was a significant positive correlation between physical activity intensity and cardiorespiratory fitness (r = 0.642, p < 0.001), a moderate positive correlation between physical activity intensity and sleep duration (r = 0.468, p < 0.001), and a significant correlation between cardiorespiratory fitness and sleep duration (r = 0.537, p < 0.001). This study confirms that maintaining adequate physical activity levels plays an important role in improving cardiorespiratory fitness and increasing optimal sleep duration in college students.